"Sacrifice" As Form of Dakwah (Case Study Of Tabligh Religious Thought) - Halim, Harifuddin; Usman, Ahmad; Asmirah, Asmirah; Masdar, Muhammad (Palakka : Media and Islamic Communication, 2021)
This study aims to reveal the forms of sacrifice as a model of preaching carried out by members of the Tabligh group. They do this as a manifestation of their belief in the Islamic religion that they profess. This study used a quantitative method with a survey approach to the Tablighi group. This approach is appropriate in expressing one focus of study, namely sacrifice as a model for group da'wah. The data was collected using a questionnaire to 25 members of the Tabligh group related to the 'sacrifice' da'wah model they carried out. The results showed: the form of sacrifice as a model of da'wah in their beliefs in the form of sacrifice of time, sacrifice of work, sacrifice of family, sacrifice of wealth, sacrifice of self, and sacrifice of feelings. They think all of these things are material that must be sacrificed to get a reward from Allah SWT.